2015
DOI: 10.1016/j.ccell.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Evolving CAR T Cell Platform into Higher Gear

Abstract: In this issue of Cancer Cell, Zhao and colleagues test various chimeric antigen receptor (CAR) T cells to show that CD28-CD3ζ CAR T cells that constitutively express 4-1BBL promote T cell expansion and tumor eradication while reducing exhaustion. The results have important implications for the development of effective CAR T cell therapies in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Some recent reports have revealed that second-generation CARs constitutively expressing ligands for CD28 or 4/1BB (CD80 or 4/1BBL, respectively) enhance T cell activity in vivo [ 104 ]. Stephan and colleagues suggested that the 4/1BB-4/1BBL signaling pathway may more effectively enhance CAR modified-T cell activation and cytotoxicity, potentially in a bidirectional manner with direct signaling within the T cells themselves and indirect triggering of other immune cells expressing the 4/1BB domain in the TME (Fig.…”
Section: Approaches To Improve the Car-t Cell Efficacymentioning
confidence: 99%
“…Some recent reports have revealed that second-generation CARs constitutively expressing ligands for CD28 or 4/1BB (CD80 or 4/1BBL, respectively) enhance T cell activity in vivo [ 104 ]. Stephan and colleagues suggested that the 4/1BB-4/1BBL signaling pathway may more effectively enhance CAR modified-T cell activation and cytotoxicity, potentially in a bidirectional manner with direct signaling within the T cells themselves and indirect triggering of other immune cells expressing the 4/1BB domain in the TME (Fig.…”
Section: Approaches To Improve the Car-t Cell Efficacymentioning
confidence: 99%
“…Although CAR-T cells have presented great promise for clinical applications, there are two main problems that can arise: CRS and in the case of anti-CD19 CAR-T cells, B-cell aplasia and subsequent immunodepression [ 23 , 32 - 34 ]. One of the solutions used in this regard is the use of switch molecules, like rimiducid, to control CAR-T cells activity [ 35 - 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another second-generation CAR construct incorporating CD28 signaling domain proved efficiency for 21 chemotherapy-resistant B precursor ALL patients (70% complete remission rate) without encountering prolonged B-cell aplasia after. In addition, the other side effects such as CRS were reversible ( 144 ). CAR T-cell-based therapy represents external stimuli that might be significant on the immune system.…”
Section: Second-generation Car Constructs For Hematological Malignancmentioning
confidence: 99%